Preoperative diagnostics in differentiated thyroid carcinoma - Seifert, Philipp; Freesmeyer, Martin (Nuklearmedizin - NuclearMedicine, 2017)
Aim: The preoperative diagnosis of differentiated thyroid carcinomas (DTC) is particularly challenging in view of the high prevalence of thyroid nodules in the general population. Incidental diagnosis of DTC, on the other hand, can lead to reoperations and increased risk of morbidity. This study aimed to assess the prediction value of preoperative DTC dignity assessment and it’s impact on surgical approaches. Methods: We retrospectively reviewed 107 cases of DTC and subdivided them in three groups based on the preoperative dignity assessment: suspected malignancy (SM), unclear dignity (UD), and incidental findings (IF). The group differences were investigated in terms of diagnostic methods, findings, and impact on the subsequent surgical approach. Results: The patient groups consisted of n = 51 (SM), n = 32 (UD), and n = 24 (IF). The tumor size, T staging, and ultrasound (US) assessment had the largest impact on the dignity classification (each p < 0.001). Scintigraphy was performed in 80 % of the patients, fine-needle aspiration cytology (FNAC) in 28 %. Hypofunction at scintigraphy (p < 0.001) and cytology results (p < 0.01) were identified as significant predictors for group assignment. Other significant factors were the frequency of the US documentation of nodule characteristics (p < 0.001) and malignancy criteria (p < 0.01) as well as reduced thyroid-stimulating hormone (TSH) levels (p < 0.01). Frozen section (p < 0.001) and total thyroidectomy (p < 0.01) at initial surgery were performed significantly more often in the MV group. Reoperations were significantly more frequent in the IF group (p < 0.001). Conclusions: A relevant number of DTC cases was diagnosed incidentally, leading to significantly more frequent reoperations. A more systematic diagnostic approach with complete documentation of the findings according to current guidelines should be pursued.
Keywords: Differentiated thyroid carcinoma; DTC; thyroid diagnostics; thyroid surgery; incidental DTC; thyroid incidentaloma